Model Village Economy Berbasis Integrasi Sistem Informasi Desa Untuk Penguatan Ekonomi UMKM Di Desa Sokop - Aqil Farras; Hustinawati Hustinawati; Siti Hanifa Sandri; Jeki Algusri (EL-EMIR Institute, 2026)
This study aims to develop a Village Economy model based on the integration of Village Information Systems to strengthen the MSME economy in Sokop Village, Meranti Islands Regency. The study used a mixed methods approach with a sequential explanatory design with 60 respondents consisting of village officials, MSMEs, and the community. Analysis was conducted by comparing the utilization rate of the village website before and after the integration of marketplace features and digital public services. The results showed an increase in system utilization in aspects such as public information access (52% to 82%), online complaints (35% to 70%), and MSME product promotion (28% to 75%). This increase indicates that the integration of the marketplace into the village information system contributes to expanding the visibility of local products and increasing community participation in technology-based public services. Theoretically, this study enriches the study of e-government integration and the village economy through a four-component model: digital governance, digital public service, digital market integration, and digital literacy empowerment. Practically, this model can serve as an implementation reference for other villages in building an integrated technology-based economic ecosystem.